2007
DOI: 10.1002/jso.20712
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine levels in response to hepatic cryoablation

Abstract: It might be possible to evaluate the appearance of immune responses to cryosurgery by monitoring serum cytokine levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 27 publications
2
43
0
1
Order By: Relevance
“…27 So far, cytokine levels in serum of patients with breast cancer after cryoablation has not been reported, but in patients with prostate cancer it was found that IFNg and TNFa significantly increased after cryoablation in the serum, 28 while in patients with hepatic cancer TNFa and IL-10 increased significantly in the serum after cryoablation. 29 In summary, these results indicate that the production of cytokines for each cancer may be different and should be analyzed for each individual patient to develop a personalized combination therapy. Based on patient's cytokine profile, an optimal adjuvant could be selected for combining with cryoablation.…”
Section: Discussionmentioning
confidence: 96%
“…27 So far, cytokine levels in serum of patients with breast cancer after cryoablation has not been reported, but in patients with prostate cancer it was found that IFNg and TNFa significantly increased after cryoablation in the serum, 28 while in patients with hepatic cancer TNFa and IL-10 increased significantly in the serum after cryoablation. 29 In summary, these results indicate that the production of cytokines for each cancer may be different and should be analyzed for each individual patient to develop a personalized combination therapy. Based on patient's cytokine profile, an optimal adjuvant could be selected for combining with cryoablation.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have examined the outcomes of percutaneous cryoRx for HCC using CT monitoring and MR guidance, reporting that it is safe and efficacious (30). Moreover, it was found that not only was the local tumor necrotic, but also that the adjacent tumor tissue was necrotic and shrunken in HCC patients following cryoRx, which was regarded as reflecting ectopic tumor suppression (16). We report that following cryoablation for small HCC the 1-, 2-and 3-year recurrence-free survival rates were 72, 56 and 43%, respectively (25).…”
Section: Discussionmentioning
confidence: 99%
“…Although the value of cryotherapy (cryoRx) in HCC is not yet as well established as that of RFA, cryoRx has been found to be more advantageous for improving immunity following treatment compared to RFA. Osada et al found that not only the local tumor, but also the adjacent tumor tissue was necrotic and shrunken in HCC patients following cryoablation, which was regarded as ectopic tumor suppression (16). This response may be associated with the release of tumor antigens, resulting in the host production of anti-tumor antibodies (17).…”
Section: Introductionmentioning
confidence: 99%
“…125 The results also demonstrate that immunogenic TAAs remain available in the tumor debris after HIFU ablation for effective presentation by DCs, increasing the number and activity of TILs. 126 …”
Section: Physical Treatmentsmentioning
confidence: 99%
“…Recent clinical studies revealed the upregulation of serum cytokine levels and generation of tumor-specific T-cells following cryoablation. 126,127 The simplicity of cryoablation coupled with its minimal negative effects on the immune system make this procedure an attractive candidate for combination regiment with immunotherapy. 124 Chemotherapy Long-standing dogma suggested that myelosuppressive effects of chemotherapy would prevent its application in combination with immunotherapy.…”
Section: Cryoablationmentioning
confidence: 99%